A comparison between two discordancy tests to identify outlier in Wrapped Normal (WN) samples - Nurisha Mohd Zulkefli,; Adzhar Rambli,; Mohamad Ismeth Khan Azhar Suhaimi,; Ibrahim Mohamed,; Raiha Shazween Redzuan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study focuses on comparing the performance of the Robust Circular Distance (RCDU*) (simplified version) and A statistics in detecting a single outlier in the Wrapped Normal (WN) samples. Firstly, this study proposes a simplified version of RCDU statistic. Then, the paper generates the cut-off points for both statistics taken from WN samples via a simulation study. This study also evaluates the performance of both statistics using the proportion of a correct outlier detection. As a result, for a small sample size, the performance of RCDU* and A statistics do not have a huge difference. However, for a large sample size of n=250, A statistic performs slightly better than RCDU* statistic. As an illustration of a practical example, both statistics successfully detected one outlier present in the wind direction data at Kota Bharu station.